P290 Baseline monocyte count may help make a diagnosis of giant cell arteritis: results of routinely collected audit data from two centres. (23rd April 2022) - Mulhearn, Ben; Ellis, Jessica; Somoskeoy, Tamas; Bourn, Alexandra; Knights, Sally; Skeoch, Sarah; Tansley, Sarah
Abstract: Background/Aims: Giant cell arteritis is a large vessel vasculitis classically affecting the head and neck. If untreated it leads to permanent vision loss. Diagnosis of GCA is based on clinical judgement of the likelihood of GCA combined with blood tests, imaging and/or temporal artery biopsy. Biopsy is considered the gold standard, but access has been restricted at many centres during the pandemic. It is recognised that some patients will have a negative ultrasound but still deemed to have GCA based on the clinical history and physical findings. In a previous audit at Yeovil District Hospital, we evaluated factors associated with biopsy-proven GCA to explore how routine tests help guide diagnosis, particularly in cases where initial imaging is negative and biopsy is unavailable. This audit found that the baseline monocyte count had good diagnostic accuracy compared to classical inflammatory markers and clinical parameters (area under the curve [AUC] 0.81, 95% confidence interval [CI] 0.67-0.95, p = 0.0034). Although novel, this finding involved a small number of patients and requires further investigation. We aimed to repeat the audit in a larger cohort and investigate blood biomarkers, including monocytes, in GCA patients as defined by physician diagnosis. Methods: At the Royal National Hospital for Rheumatic Diseases, data were collected retrospectively on patients that were referred between 01/2020 and 09/2021 from hospital records, the GP referral, and pathology systems. A positive diagnosis of GCA was determined by presentation, inflammatory response, vascular imaging and clinical course, and was confirmed by a rheumatologist. Sensitivity, specificity and ROC analysis were calculated for each biomarker, including monocyte count, platelets, CRP, and plasma viscosity (PV). Results: 301 referrals were made to the GCA clinic over the period audited. 109/301 (36%) were diagnosed with GCA, of which 98/109 (90%) had imaging studies and 62/98 (67%) had had a positive test. 55/301 referrals had already started glucocorticoids before baseline blood monitoring. ROC analysis found monocyte count was predictive of GCA (AUC 0.83, 95%CI 0.77-0.90, p < 0.0001). A cut-off value of ≥ 0.9 x 106/L gave a specificity of > 95% and a positive likelihood ratio (LR) of 10 for a diagnosis of GCA in this cohort. However, monocytes were heavily influenced by glucocorticoids and after ≥1 dose there was a drop in sensitivity of 20%. Conclusion: In a second, larger cohort of GCA cases, we have again identified monocytes as a potential biomarker of GCA. However, they appear to be highly sensitive to glucocorticoids and their use as a biomarker may be limited to glucocorticoid-naïve patients. A prospective research study is now being planned to take these findings further. Disclosure: B. Mulhearn: None. J. Ellis: None. T. Somoskeoy: None. A. Bourn: None. S. Knights: None. S. Skeoch: None. S. Tansley: None.